(untitled) (Baghdad Science Journal, 2021)
Spray pyrolysis technique (SPT) is employed to synthesize cadmium oxide nanostructure with 3% and 5% Cobalt concentrations. Films are deposited on a glass substrate at 350 ᵒC with 150 nm thickness. The XRD analysis revealed a polycrystalline nature with cubic structure and (111) preferred orientation. Structural parameters represent lattice spacing, crystallite size, lattice parameter and dislocation density. Homogeneous surfaces and regular distribution of atoms were showed by atomic force microscope (AFM) with 1.03 nm average roughness and 1.22 nm root mean square roughness. Optical properties illustrated a high transmittance more than 85% in the range of visible spectrum and decreased with Co concentration increasing. The absorption coefficient values decreased with increasing wavelength and the prepared films had absorption coefficient values greater than 104 cm-1. The optical energy gap values for allowing direct transition (ADT) varied from 2.78 to 2.63 eV with increasing Co concentration, while the energy gap for allowing indirect transition (AIDT) varied from 1.85 to 1.6 eV with Co concentration.